Labor inclusion of women with disabilities in Mérida, Yucatán, Mexico - Zimbrón Pérez, Guadalupe (2024)
The objective of this research is to analyze the use of the method Empleo con Apoyo (ECA) in companies in Merida, Yucatan, Mexico, that make labor inclusion of women with disabilities as a strategy to improve their permanence in their jobs. A qualitative methodology was used through an interpretative case study in the period from October 2022 to September 2023. The results describe the forms of discrimination suffered for this people in their journey to get a job.